Adherence and Population Pharmacokinetic Properties of Amodiaquine When Used for Seasonal Malaria Chemoprevention in African Children. Issue 5 (31st December 2019) - Ding, Junjie; Coldiron, Matthew E.; Assao, Bachir; Guindo, Ousmane; Blessborn, Daniel; Winterberg, Markus; Grais, Rebecca F.; Koscalova, Alena; Langendorf, Celine; Tarning, Joel
Abstract : Poor adherence to seasonal malaria chemoprevention (SMC) might affect the protective effectiveness of SMC. Here, we evaluated the population pharmacokinetic properties of amodiaquine and its active metabolite, desethylamodiaquine, in children receiving SMC under directly observed ideal conditions ( n  = 136), and the adherence of SMC at an implementation phase in children participating in a case‐control study to evaluate SMC effectiveness ( n  = 869). Amodiaquine and desethylamodiaquine concentration‐time profiles were described simultaneously by two‐compartment and three‐compartment disposition models, respectively. The developed methodology to evaluate adherence showed a sensitivity of 65–71% when the first dose of SMC was directly observed and 71–73% when no doses were observed in a routine programmatic setting. Adherence simulations and measured desethylamodiaquine concentrations in the case‐control children showed complete adherence (all doses taken) in < 20% of children. This result suggests that more efforts are needed urgently to improve the adherence to SMC among children in this area.